Hôtel-Dieu in Paris: origins and appearance of the first religious nurses of the history - cristina teresa morales; javier garcia berrocal (Universidad de Alicante, 2013)
The objective of the present study is to discover and disclose the history of the Hôtel-Dieu in Paris and, at the same time, the history of the Agustinian´s Sisters, nurses of the mentioned hospital. The methodology used to carry out the study was an extensive literature research, translation, reading, analysis and discussion of the documents we find during the research. The conclusions tell us about the difficulties of the occupation, about how long one person could take to complete studies and to became fully professional in this area (up to 26 years), and also talks about how the functions between some occupations and others was delimitated.